Spectral and Cathodoluminescence Decay Characteristics of the Ba1−xCexF2+x (x = 0.3–0.4) Solid Solution Synthesized by Precipitation from Aqueous Solutions and Fusion; Photonics; Vol. 10, iss. 9 - Kuznetsov S. V. Sergey Vladimirovich; Yasyrkina D. S. Darjya Semenovna; Valiev D. T. Damir Talgatovich; Stepanov S. A. Sergey Aleksandrovich; Aleksandrov A. A. Aleksandr Aleksandrovich; Batygov S. Kh. Sergey Khacheturovich; Voronov V. V. Valery Veniaminovich; Konyushkin V. A. Vasily Andreevich; Nakladov A. N. Andrey Nikolaevich; Ermakova Yu. A. Yuliya Aleksandrovna; Fedorov P. P. Pavel Pavlovich (2023, 2023)
Title screen